Maternal Circulating Exosomal miRNAs as Non-invasive Biomarkers for the Prediction of Fetal Ventricular Septal Defect - Jin, Yuxia; Ai, Ling; Chai, Xiaojun; Tang, Ping; Zhang, Weihua; Yang, Li; Hu, Yue; Xu, Ying; Li, Suping (Frontiers in Genetics, 2021)
Objective: This study aimed to identify maternal circulating exosomal miRNAs as potential non-invasive biomarkers for the early detection of fetal ventricular septal defects (VSDs). Methods: In total, 182 pregnant women, comprising 91 VSD cases and 91 matched controls, were included in this study. Exosomes were isolated; dysregulated exosomal miRNAs were profiled using next-generation sequencing. Differential abundance of miRNAs was verified using quantitative real-time polymerase chain reaction (qRT-PCR). Diagnostic accuracy was evaluated by constructing receiver operating characteristic (ROC) curves. Results: In total, 77 serum exosomal miRNAs were found to be differentially expressed in the VSD group compared to their expression in the control group. Among these, five downregulated exosomal miRNAs were validated using qRT-PCR. hsa-miR-146a-5p was identified to be capable of distinguishing VSD cases from controls (area under the ROC curve [AUC]: 0.997; p < 1.00E-05). Conclusion: Circulating exosomal miRNAs, particularly hsa-miR-146a-5p, may be predictive biomarkers for the non-invasive prenatal diagnosis of fetal VSDs.